Reform Regulation of Novum in Criminal Judges in an Effort to Provide Legal Certainty - Saputra, Rian; Ardi, Muhammad Khalif; Pujiyono, Pujiyono; Firdaus, Sunny Ummul (Universitas Negeri Semarang, 2021)
The research stems from Decision Number 224 PK/PID.SUS/2018 which grants the application for judicial review (hereinafter abbreviated as PK) by a suspected narcotics abuser with a novum (new evidence) in the form of previous judges' decisions. In this case, this study aims to conceptualize how the regulation of PK legal remedies in criminal cases should be. This research is a normative legal research, the approach used is a case approach, a comparative approach, and a conceptual approach, with a literature study research technique. After knowing the arguments for the admissibility of submitting a PK in the form of a District Court Decision, the author makes several comparisons with the Criminal Procedure Code (America and France), and concludes based on this comparison that the use of the basis for submitting a PK should be regulated clearly and firmly in the Criminal Procedure Code, because the two countries in its criminal procedural law it expressly states that the submission of a PK must be based on new facts and evidence which, if presented at the previous trial, has the potential to reduce or even abort the prosecution's charge